The brain tumor not-for-profit and charity experience of COVID-19: reacting and adjusting to an unprecedented global pandemic in the 21st century. (7th December 2020) - Amidei, Christina; Arzbaecher, Jean; Maher, Mary Ellen; Mungoshi, Christine; Cashman, Rosemary; Farrimond, Stuart; Kruchko, Carol; Tse, Chris; Daniels, Maureen; Lamb, Sharon; Granero, Anita; Lovely, Mary; et al.
Abstract: Background: The Coronavirus Disease 2019 (COVID-19) pandemic has affected individuals as well as disease-specific brain tumor organizations. These organizations around the world exist to address unmet needs for patients and caregivers they serve. The direct impact of the pandemic on these organizations constitutes significant collateral damage. In order to better understand the effects of the COVID-19 pandemic on brain tumor organizations, the International Brain Tumour Alliance (IBTA) carried out an international survey to identify organizational changes induced by the virus and approaches adopted to address challenges. Methods: A 37-question online survey consisting of categorical and qualitative questions was developed and circulated to 130 brain tumor organizations across the world. Seventy-seven organizations from 22 countries completed the survey (59% return rate). Descriptive statistics and content analysis were used to present the results. Results: Responses fell into the following 3 categories: (1) organizational characteristics, (2) impact of COVID-19 on services, and (3) COVID-19 impact on financial and human resources within organizations. Although organizational characteristics varied, common concerns reported were activity disruption which impacted organizations' abilities to offer usual services and challenges to sustaining funding. Both financial and human resources were stressed, but integral adaptations were made by organizations to preserve resources during the pandemic. Conclusions: Although brain tumor organizations have been impacted by the COVID-19 pandemic, organizations quickly adjusted to this unprecedented global healthcare crisis. Nimble reactions and flexibility have been vital to organization sustainability. Innovative approaches are required to ensure organizations remain viable so that needs of brain tumor community at large are met.